2017
DOI: 10.1371/journal.pone.0176166
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish GDNF and its co-receptor GFRα1 activate the human RET receptor and promote the survival of dopaminergic neurons in vitro

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a ligand that activates, through co-receptor GDNF family receptor alpha-1 (GFRα1) and receptor tyrosine kinase “RET”, several signaling pathways crucial in the development and sustainment of multiple neuronal populations. We decided to study whether non-mammalian orthologs of these three proteins have conserved their function: can they activate the human counterparts? Using the baculovirus expression system, we expressed and purified Danio rerio RET, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…1J-K). In this assay GDNF usually increases luciferase activity in GFRα1/RET expressing cells by 50-100 fold (Sidorova et al , 2010, 2017; Saarenpää et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1J-K). In this assay GDNF usually increases luciferase activity in GFRα1/RET expressing cells by 50-100 fold (Sidorova et al , 2010, 2017; Saarenpää et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…GDNF (10 ng/ml) increased the number of TH-positive cells in culture by 1.8 fold (P = 0.0207, Dunnett’s post hoc test) (Figure 2A, B). Important to note, that the bell-shaped dose-response curves are common for neurotrophic factors in general and for GDNF in particular (Hou et al , 1996; Saarenpää et al , 2017). Therefore, the lack of increase in dopamine neuron survival in response to the higher doses of BT13 is expected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially for efn-As, they have an overall sequence similarity as high as 80% among their orthologs ( S1 Fig ). Our recent study found that zebrafish GDNF/GFRα1 could activate human RET, revealing the structural and functional conservation of RET from an evolutionary perspective [ 24 ]. Because mammalian RETs are prone to misfold [ 25 , 26 ] and thus difficult to produce, we wanted to determine if the binding of RET to efn-A5 is conserved in lower vertebrates, for example zebrafish, and characterize their binding behavior to elucidate the underlying molecular mechanism of the reverse signaling of efn-A5.…”
Section: Introductionmentioning
confidence: 99%